Governance of Developmental Public Policies in the Face of Emerging Climate Changes in the Arabian Gulf Region (Saudi Arabia as a Model) - Al-Dabbagh, Zeyad Samir; Arnout, Boshra Esmaeel; Hussein, Ghufran Younus (Dirasat: Human and Social Sciences, 2025)
Objectives: The research's objectives lie in identifying the governance of public development policies and their role in confronting the emerging climate changes currently occurring, which may have severe catastrophic risks that include many levels, and the necessity of implementing these policies. Methods:: The research relied on the analytical method, which included analyzing general development policies related to climate change in the Arabian Gulf region, and the inductive approach, which included observing and studying the impact of emerging climate changes on the reality of that region. Results: The Arab Gulf countries have actively sought individual and cooperative efforts to find optimal solutions and methods to mitigate climate change's severity. Saudi Arabia, in particular, has effectively managed its public policies and implemented various measures to address climate-related issues. These measures include expanding green zones, diversifying financing, and actively participating in global agreements like the Paris Climate Agreement. Conclusions: The issue of public policy governance to reduce the adverse effects of climate change in the Arabian Gulf has become an urgent issue, as local governments and public policymakers in these countries can play an essential role in planning and implementing ideas and initiatives that may limit the effects of climate change, through sound investments, for resources, support, and partnerships with local, regional, and international authorities, and the importance of raising community awareness and expanding its awareness of adapting to emerging climate changes.